¿Por qué no queremos a los inmigrantes? La metáfora como reflejo de las relaciones sociales - Nowakowska, Anna (Neophilologica, 2007)
The article analyses selected examples of the SN1 is SN2 generic metaphors that refer to the phenomena of immigration and racism. It appears that in majority of the analyzed metaphors, the SN2 position is occupied by the so called “domesticated term”, which, owing to its high degree of conventionality, assures the proper interpretation of a given metaphor. Furthermore, though of a generally neutral character, the term SN2 acquires a pejorative meaning when it enters in the metaphorical relation with the term SN1, and at the same time expresses the causes of negative attitudes towards immigrants. These causes, in their turn, seem to reflect such social phenomena as hidden racism and an actual group conflict. This allows us to assume that language discrimination, or the so called political incorrectness, is not a question of single words, but of the relations existing between them.